CYBERCRIME AND INTERNATIONAL JURISDICTION: A COMPARATIVE STUDY OF LEGAL RESPONSES IN INDIA (International Journal of Food and Nutritional Sciences, 2023)
Cybercrime has become one of the most significant global threats in the digital age, challenging traditional legal frameworks and law enforcement mechanisms. Due to its transnational nature, cybercrime often involves perpetrators, victims, and digital evidence spread across multiple jurisdictions, leading to complex legal disputes over enforcement authority. This paper provides a comparative analysis of cybercrime legal frameworks in India, the United States, the European Union, China, and the United Kingdom. It examines key jurisdictional principles, including territoriality, nationality, and the effects doctrine, and evaluates the effectiveness of existing mutual legal assistance treaties (MLATs), data protection laws, and international cybercrime enforcement mechanisms.